ADAPTASI MASYARAKAT PENDATANG (ETNIK MADURA SAMBAS) DENGAN PENDUDUK ASLI (Tanjungpura University, 2021)
The purpose of this study was to determine the Adaptation of Newcomers (Madura Sambas Ethnic) with Indigenous Peoples: A Study in Madu Sari Village, Sungai Raya District, Kubu Raya Regency. The background of this research is the number of ethnic Madurese after the ethnic riots in Sambas who fled and settled in Madu Sari Village, Kecamtan Sungai Raya District, Kubu Raya Regency. In the process of adaptation, the Madurese Sambas (immigrants) and indigenous people (local people) experience many problems, especially problems of interaction related to religion, socio-culture, economy, and so on. The purpose of this research was to describe how the process of adaptation between Madurese Sambas (newcomers) and local indigenous people in Madu Sari Village. The method used in this research is the descriptive method with a qualitative approach. In connection with this, the results of the study show that there is a good adaptation between the immigrant Madurese ethnicity and the local population, namely the immigrant Madurese ethnicity always maintains a friendship with local villagers, behaves politely, is friendly, and participates in mutual cooperation on major holidays. is in the village.